2017
DOI: 10.1017/s0033291717000988
|View full text |Cite
|
Sign up to set email alerts
|

Insular pathology in young people with high-functioning autism and first-episode psychosis

Abstract: The shared reduced volume and thickness in the anterior and posterior regions of the insula in ASD and FEP provides the first tentative evidence that these conditions share structural pathology that may be linked to shared symptomatology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
(59 reference statements)
2
21
0
2
Order By: Relevance
“…For instance, lower grey matter volume in the limbic-striato-thalamic circuitry is common to schizophrenia and autism-spectrum disorders, 16 and reduced volume and thickness of the insula have been found in patients with first-episode psychosis and in high-functioning patients with autism-spectrum disorders. 17 Similar alterations to the white matter integrity of the left fronto-occipital fasciculus have recently been found in patients with schizophrenia and in patients with autism-spectrum disorders. Scaffolding proteins represent an evolutionary solution to controlling the specificity of information transfer in intracellular networks.…”
Section: Introductionsupporting
confidence: 55%
“…For instance, lower grey matter volume in the limbic-striato-thalamic circuitry is common to schizophrenia and autism-spectrum disorders, 16 and reduced volume and thickness of the insula have been found in patients with first-episode psychosis and in high-functioning patients with autism-spectrum disorders. 17 Similar alterations to the white matter integrity of the left fronto-occipital fasciculus have recently been found in patients with schizophrenia and in patients with autism-spectrum disorders. Scaffolding proteins represent an evolutionary solution to controlling the specificity of information transfer in intracellular networks.…”
Section: Introductionsupporting
confidence: 55%
“…We previously reported on a transdiagnostic anterior and posterior insular volume deficit in the ASD and EO‐FEP sample (sample 1) (Parellada et al, ). The current study extends these findings by showing that insular volume deficits are caused by decreases in SA and, to a lesser degree, by deficits in CT and that these two types of deficits are largely independent (i.e., spatial nonoverlap) from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and meta‐analyses conducted in either ASD or psychotic disorders have reported additional cortical and subcortical deficits in several regions, including frontal regions, the cingulum, the hippocampus, and the amygdala, among others (Bora et al, ; Ecker et al, ; Radua et al, ; Via, Radua, Cardoner, Happe, & Mataix‐Cols, ). However, incongruent results have been reported when the neuroanatomy of individuals with ASD, psychotic disorders and typically developing subjects (TD) was directly (i.e., within‐study, single scanner and acquisition protocol) compared (Katz et al, ; Mitelman et al, ; Parellada et al, ; Radeloff et al, ). The majority of these studies focused on adults and used volumetric brain measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Structural neuroimaging studies have linked poor insight to reduced volume in several areas, including frontal 104,106,107 , temporal 107,108 , parietal 104,107 and occipital 107 regions, the thalamus 101 , basal ganglia 104 and cerebellum 107 , in both first-episode psychosis 109 and chronic schizophrenia 107 .…”
Section: Abnormalities In Brain Function As a Root Of Poor Insightmentioning
confidence: 99%